Crystallization behavior and mechanical properties of nano-CaCO3/β-nucleated ethylene-propylene random copolymer composites - W. H. Ruan; J. H. Mai; M. Z. Rong; M. Q. Zhang; T. Barany (eXPRESS Polymer Letters)
To provide ethylene-propylene random copolymer (PPR) with balanced mechanical properties, β-nucleating agent and CaCO3 nanoparticles are incorporated into PPR matrix by melt blending. It is found that crystallization rate and relative content of β-crystal increase with the addition of β-nucleating agent together with nanoparticles. Size of PPR spherulite is greatly reduced, and a specific morphology appears, in which α-crystal lamella is grown upon the β-nucleus. The results suggest that both β-nucleating agent and nano-CaCO3 have heterogeneous nucleation and synergistic effects on β-nucleation of PPR. Mechanical characterization shows that mechanical properties of PPR can be tuned by incorporation of β-nucleating agent and nano-CaCO3 particles. Under suitable compositions, low temperature impact strength and high temperature creep resistance of PPR, the bottlenecks of application of such material, can be simultaneously improved without sacrificing the Youngs’modulus and tensile strength.